PENINGKATAN HASIL BELAJAR IPA SISWA MELALUI MODEL INKUIRI DI MIS PARMIYATU WASSA’ADAH PERCUT SEI TUAN - NIRWANA ANAS (Universitas Islam Negeri Sumatera Utara, 2017)
This study aims to determine: (1) Student learning outcomes before applying Inquiry learning model on science subjects, (2) Student learning outcomes after applying Inquiry learning model on science subjects, (3) Improving the application of student learning outcomes after using learning model Inquiry on science subjects, Pesawat Sederhana topic in the fifth grade students of MIS Parmiyatu Wassa'adah. This research uses Classroom Action Research (CAR) with three cycles. The subjects of the study were students in the fifth grade students of MIS ParmiyatuWassa'adah 29 students.Based on the results of this study can be concluded that: (1) Student learning outcomes before applying Inquiry model on pre-action is there are 3 complete students and 26 other students who have not completed with the average grade is 48.97 with the percentage of completeness Learning is 10.34% (2) Students' learning outcomes after applying the Inquiry model in the first cycle, there are 14 complete students and 15 other students who have not finished with the average is 69.31 with the percentage of learning result completeness is 48.28%. In second cycle there are 20 complete students and 9 other students who have not finished with the average is 75.86 with the percentage of learning result completeness is 68.97%. In the third cycle there are 22 students and 7 other students have not completed with the average obtained is 83.10 with the percentage of learning result completeness is 75.86%.Thus it can be concluded that the application of Inquiry learning model can improve student learning outcomes in science subjects Pesawat sederhana topic in fifth grade of MIS Parmiyatu Wassa'adah Kec. Percut Sei Tuan Kab. Deli Serdang Tahun Ajaran 2016/2017.